63 10 year follow-up study of the long term effects of ANTI-TNF therapyon bone metabolism in a cohort of ANTI-TNF naïve IBD patients. (5th April 2017) - O'Morain, N; Farrell, G; Stack, R; Hussey, M; Bailey, Y; Kiat, C; Veerappan, S; McNamara, D; O'Connor, A; Breslin, N; O'Morain, C; Ryan, BM
Abstract : Background: Anti-TNF therapy (ATT) has been shown to have beneficial effects on bone metabolism in the short term, but there is a dearth of long term prospective data. Aim: To evaluate the long term effects of ATT on bone metabolism. Method: Retrospective observational cohort study of ATT naïve IBD patients first evaluated in 2007 by DXA scan and by metabolic bone markers prior to, and one year post commencement of ATT. Patients were invited to undergo repeat DXA scan and serum bone marker measurement. Results: To date, 73% ( n=38/52) patients from the original study have been recruited for 10 year follow up. There were 3 deaths, 4 refusals, 7 uncontactable. DXA scans and serum samples have been collected on 24/38 patients. 50% were female, mean age of 44.5 years (range 27-80). 67% (n=16) Crohn's, 33% (n=8) UC. 6 patients continued with immunomodulator (IMM), 11 with ATT (Adalimumab (n=5), Infliximab (n=6)), 2 with combination therapy (ATT/IMM), 1 with 5-ASA, 4 no treatment. Mean T score prior to ATT in 2007 was −1.46 (SD +/-1.24), and 0.81 (SD +/-1.04) at 10 years. The baseline and 10 year mean T-scores were −1.53 (SD +/-1.26) and −0.70 (SD +/-1.13) for patients remaining on ATT and −0.97 (SD +/-1.27) and −0.66 (SD +/-1.01) for those off ATT. Serum analyses are in process. Conclusions: In this ongoing 10 year follow up study, results suggest that long term (>10 years) treatment with anti-TNF therapy has a beneficial effect on bone metabolism.